Personal Data Exploration with Speech on Mobile Devices - Choe, Eun Kyoung; Lee, Bongshin; Hwang, Seung-won (2018)
In this article, we envision a novel way to help people explore their personal data on mobile devices by leveraging speech interaction. Supporting visual data exploration on mobile devices pertains to two constraints. First, mobile devices’ small screen cannot afford a panel of widgets. Second, exploring self-tracking data often involves entering specific date and time, or their ranges, which is tedious to do on mobile devices. These challenges can be addressed through speech because it does not require much space and is flexible enough to cover different ways to specify date and time. Moreover, common personal insight types identified from prior work allow us to narrow the scope of the speech interaction needed for personal data exploration, making it more tractable with the state-of-the-art speech recognition technology.